EVALUATION IN ISLAMIC EDUCATION MANAGEMENT (PENGERTIAN, TUJUAN, FUNGSI DAN PERAN STRATEGIS DALAM MEWUJUDKAN TUJUAN PENDIDIKAN) - Ananda Faradina; Selly Wulandary; Syafaatul Habib (As-Sulthan Journal of Education, 2025)
Evaluation in Islamic Education Management is a crucial aspect for assessing the extent to which the goals of Islamic education can be effectively achieved. This study aims to understand the definition, objectives, and functions of evaluation in supporting the realization of Islamic educational goals. The method used is a qualitative approach through library research, by reviewing various relevant sources. Islamic education aims to shape individuals who are faithful, pious, knowledgeable, and possess noble character; therefore, evaluation is necessary to measure the success of educational programs, improve teaching methods, and develop learning strategies based on Islamic values. Evaluation in Islamic education also serves as a diagnostic and corrective tool for the overall learning system, although its implementation often faces challenges such as limited human resources, time constraints, and lack of coordination among stakeholders.